Comment on “45 Sc Spectroscopy of Solids: Interpretation of Quadrupole Interaction Parameters and Chemical Shifts” - Richard, Diego (2011)
In ref 1, Alba et al. applied MAS NMR technique (using 45Sc as a probe-atom) to study the nuclear quadrupole interaction of 45Sc in X2-Sc2SiO5 and C-Sc2Si2O7 and in scandium sesquioxide (Sc2O3). To obtain a simple model that links the local symmetry around the probes with the observed hyperfine parameters, the authors have compared experimental quadrupole parameters with electrostatic calculations. In particular, they showed that point-charge calculations (PCM) can approximate the electric field gradient (EFG) tensor to a sufficiently good level to assign their NMR hyperfine interactions. Discrepancies between the predicted EFGs and the experimental values were attributed to unreliable determination of the structures.